2008
DOI: 10.2176/nmc.48.57
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognosis of Brain Metastases From Gynecological Cancers

Abstract: Brain metastases from gynecological cancers were retrospectively investigated in 18 patients who were treated between 1985 and 2006. Six patients received surgical resection followed by radiotherapy, and 12 patients received only radiotherapy. The median survival for all patients was 4.1 months (range 0.7-48.2 months), and the actuarial survival rates were 11% at both 12 months and 24 months. Univariate analysis showed that treatment modality, extracranial disease status, total radiation dose, number of brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 41 publications
0
44
2
2
Order By: Relevance
“…On the other hand, female genital tract is uncommon sources of brain metastases (16) and thus, there has been limited information on prognostic factors (17)(18)(19)(20). Nasu et al conducted a multi-institutional cooperative study with the largest data based on 139 cases of brain metastases from gynecological malignancies and showed that good performance status, absence of extracranial disease, single brain metastasis, ovarian origin, implementation of definitive treatments were independent favorable prognostic factors (17).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, female genital tract is uncommon sources of brain metastases (16) and thus, there has been limited information on prognostic factors (17)(18)(19)(20). Nasu et al conducted a multi-institutional cooperative study with the largest data based on 139 cases of brain metastases from gynecological malignancies and showed that good performance status, absence of extracranial disease, single brain metastasis, ovarian origin, implementation of definitive treatments were independent favorable prognostic factors (17).…”
Section: Introductionmentioning
confidence: 99%
“…The most common sites of extra-peritoneal disease qualifying for stage FIGO IV are malignant pleural effusion in 33-53%, liver in 14-26%, subcutaneous/abdominal wall in 10-41%, and extra-abdominal lymph nodes in 5-44% [5][6][7][8][9]; brain metastases (0.3-2.2% [10]) and bone involvement (b2% [11,12],) are uncommon (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…These authors conclude that surgical resection of the brain metastasis is not indicated for this kind of lesion, but we trust that it is not indicated in the same clinical conditions instead of in this disease, given that the patient was in the RTOG RPA class III, and neurosurgery in this case is questionable. Even in the large series by Ogawa et al [15] pretreatment clinical condition and treatment details are not available for all patients, but overall survival ranged between 0.7 and 28.4 months. When reviewing the more recent literature, it appears that only few case reports exist, and that clinical data are often not complete, so that we cannot confirm or deny if neurosurgical procedure is effective for patients with the classical RTOG RPA parameters (see Table 1).…”
Section: Discussionmentioning
confidence: 98%